Helical twisting in cholesterics doped by banana-shaped molecules - Serbina, M.I.; Maksimenko, S.I.; Kondratyeva, R.V.; Derkach, L.G.; Novikova, N.S.; Lisetski, L.N. (Functional Materials, 2012)
Helical pitch vs. temperature measurements were carried out for cholesteric liquid crystal matrices of different types doped with a set of banana-shaped compounds. The effects of these dopants on the helical pitch were found to be essentially different for systems based on cholesterol esters and for induced cholesterics based on twisted nematics. In the first case, all the dopants used decreased the helical pitch, i.e., caused additional helical twisting, with its magnitude varying for different dopants. In the second case, with matrices based on chiral R-811 and S-811 in cyclohexanecarboxylic acids (CHCA) and 5CB, unwinding of the helix was generally observed. For one of the dopants, however, namely, for l-[4-(4-dodecyloxybenzoyloxy)benzoyloxy]-3-[4-(4-nonylbenzoyloxy)benzoyloxy] ben¬zene, additional twisting was noted in matrices with CHCA close to the isotropic transition point, and in matrices with 5CB — in all the temperature range. The results obtained can be considered as important arguments in the controversial issue of chiral properties of banana-shaped compounds in liquid crystal phases.